1992
DOI: 10.1038/ng1092-113
|View full text |Cite|
|
Sign up to set email alerts
|

A trithorax–like gene is interrupted by chromosome 11q23 translocations in acute leukaemias

Abstract: Some acute lymphocytic leukaemias, particularly those in young children, are associated with a t(4;11)(q21;q23) reciprocal translocation. We have cloned the translocation breakpoint on chromosome 11q23 and isolated corresponding RNA transcripts from this region. The translocation occurs within a cluster of Alu repetitive elements located within an intron of a gene that gives rise to 11.5 (kb) transcript spanning the translocation breakpoint. The 11.5 kb transcript encodes a protein that is highly homologous to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
271
1
2

Year Published

1993
1993
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 444 publications
(276 citation statements)
references
References 32 publications
2
271
1
2
Order By: Relevance
“…This locus shows homology to sequences within the Drosophila 'trithorax' gene, a developmental regulator. 7,8 As these aberrations were found in AML as well as acute lymphoblastic leukemia (ALL), the gene was called mixedlineage leukemia. 9 Recent studies show that the MLL group itself is genetically and clinically heterogeneous, as more than 60 different translocation partners of the MLL gene with differences in outcome have been described to date.…”
Section: Introductionmentioning
confidence: 99%
“…This locus shows homology to sequences within the Drosophila 'trithorax' gene, a developmental regulator. 7,8 As these aberrations were found in AML as well as acute lymphoblastic leukemia (ALL), the gene was called mixedlineage leukemia. 9 Recent studies show that the MLL group itself is genetically and clinically heterogeneous, as more than 60 different translocation partners of the MLL gene with differences in outcome have been described to date.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] Since the first descriptions of t(4;11) in acute lymphoblastic leukemia (ALL) in the latter half of the 1970s, 9-11 more than 350 cases with this translocation have been reported. 5 Recent molecular genetic investigations have revealed that abnormalities involving 11q23 often lead to rearrangement of the MLL (ALL1, HRX, HTRX1) gene [12][13][14][15][16] and that the t(4;11) results in a fusion between the MLL and the AF4 (FEL, LTG4, MLLT2) genes. [17][18][19][20][21] The identification of this chimeric transcript, which occasionally is also detected in leukemias lacking the t(4;11) cytogenetically, has provided the necessary information to establish reverse-transcriptase polymerase chain reaction assays for rapid and sensitive detection of the abnormality and for disease monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of chromosomal translocations a ecting chromosome 11 at band q23 in leukaemias has shown that these events involve fusions between the human trithorax (MLL) gene (Djabali et al, 1992;Gu et al, 1992;Tkachuk et al, 1992;Ziemin-van der Poel et al, 1991) and a variety of partner genes each providing a COOH region to the resultant fusion protein. These translocations result in in-frame fusions suggesting an important role for the di erent COOH regions in the oncogenic transformation.…”
Section: Introductionmentioning
confidence: 99%